IMPLEMENTASI PTK BERBASIS LESSON STUDY MELALUI PENERAPAN MODEL THINK-PAIR-SHARE DENGAN MENGGUNAKAN KOMIK PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TINGKAT MADRASAH ALIAH - Usman Usman; Muh. Zaini Hasanul Muttaqin (JURNAL ASIMILASI PENDIDIKAN, 2024)
The problem of student learning outcomes that do not meet student achievement standards in biology material is the main basis for carrying out lesson study-based classroom action research. This research is qualitative research by applying the think pair share learning model using learning comics. From the research results, it was obtained that the percentage of learning implementation by teachers increased from 81.67% in the first cycle to 90% in the second cycle, then the presentation of learning implementation by students from 88.33% in the first cycle to 93.33% in the second cycle. Meanwhile, student learning outcomes increased from the average percentage of student completion from 32% in the first cycle to 72% in the second cycle